Identifying the causal effect of child marriage on unmet needs for modern contraception and unintended pregnancy in Nepal: a cross-sectional study using propensity score matching - Masamine Jimba; Ken Ing Cherng Ong; Anand Tamang; Kazutaka Sekine; Rogie Royce Carandang (BMJ Open)
Objectives This study aimed to investigate whether child marriage had causal effects on unmet needs for modern contraception, and unintended pregnancy, by estimating the marginal (population-averaged) treatment effect of child marriage.Design This study used secondary data from the Nepal Demographic and Health Survey 2016. Applying one-to-one nearest-neighbour matching with replacement within a calliper range of ±0.01, 15–49 years old women married before the age of 18 were matched with similar women who were married at 18 or above to reduce selection bias.Setting Nationally representative population survey data.Participants The sample consisted of 7833 women aged 15–49 years who were married for more than 5 years.Outcome measures Unmet needs for modern contraception and unintended pregnancy.Results The matching method achieved adequate overlap in the propensity score distributions and balance in measured covariates between treatment and control groups with the same propensity score. Propensity score matching analysis showed that the risk of unmet needs for modern contraception, and unintended pregnancy among women married as children were a 14.3 percentage point (95 % CI 10.3 to 18.2) and a 10.1 percentage point (95 % CI 3.7 to 16.4) higher, respectively, than among women married as adults. Sensitivity analysis indicated that the estimated effects were robust to unmeasured covariates.Conclusions Child marriage appears to increase the risk of unmet needs for modern contraception and unintended pregnancy. These findings call for social development and public health programmes that promote delayed entry into marriage and childbearing to improve reproductive health and rights.